Self-Healing of Hot Bituminous Mixtures by Using Microwaves - سالم عماد; بسام سلطان (Latakia University Journal -Engineering Sciences Series, 2023)
The research aims to study the self-healing property of hot bituminous mixtures when subjected to electromagnetic induction by microwave waves. The materials included in the design of bituminous mixtures were characterized, and then prismatic samples were prepared, modified by adding steel shavings with different percentages of the weight of fine aggregate then, the flexural tensile experiment was conducted to determine the initial fracture strength of these samples. After that, the samples were heated by a microwave device for three periods of time and the temperature reached was recorded. the flexural tensile experiment was repeated to determine the fracture strength of these samples after each induction period. The results showed that the minimum temperature at which the healing begins is (50°C) after an induction time (60s) and the highest healing rate reached by the samples was (85.9%) at an addition rate of (2%) and a heating time of (180s).